N-doped and sulfur vacancy-rich TiO2@SnS2 nanoporous arrays for the plasmonic photocatalytic H2 evolution. (26th May 2023) - Guo, Limin; Hu, Runze; Zhong, Caifu; Wang, Xinxin; Liu, Jiaming; Wang, Xiaohui
Abstract: An elegant templating method has been developed for the rational design and synthesis of hierarchical SnS2 nanoclusters composed of ultrathin nanosheets and embedded inside TiO2 nanoporous arrays. Herein, benefiting from their unique structural merits and metal-like plasmonic activity, the TiO2 @SnS2 heterostructures exhibit enhanced photocatalytic H2 evolution properties in terms of good cycling performance. S vacancies and N-doping are proved to be vitally important to the electronic structures and bandgap of SnS2, thus influence the plasmonic property and separation of photo-carriers. The optimized TiO2 @6nmSnS2 /N nanoporous arrays give an ultra-high H2 yield rate of 285 μmol h −1 cm −2 under a low catalyst loading mass, that comparable to most noble metal catalysts. Remarkable cycling performance with a capability retention of 90% is achieved after 30 h under solar light illumination. As an innovative exploration, this study demonstrates that the photocatalytic activities of nonmetal, earth-abundant SnS2 can be enhanced with plasmonic effect, which may serve as an excellent catalytic agent for solar energy conversion to chemical fuel. Graphical abstract: Image 1 Highlights: A SnS2 /TiO2 heterostructured was designed by anodization and PVD process. The heterostructure exhibiteds excellent H2 evolution efficiency and stability. S vacancy and N-doping can enhance the photo carrier separation and transfer.